THE INFLUENCE OF SELF EFFICACY, JOB INSECURITY, AND JOB DEVELOPMENT ON JOB SATISFACTION THROUGH JOB MOTIVATION AS AN INTERVENING VARIABLE AT PT. BEAUTIFUL FASHION SWAKARYA, TANJUNGPINANG CITY - Hidayati Eka Putri, Fanny; Satriawan, Bambang; Indrawan, M.Gita; Titik Windayati, Diana; Fatahurrazak, Fatahurrazak (CV. Radja Publika, 2022)
A person's efficacy determines how much effort is expended and how the individual survives in the face of obstacles. The stronger the perception of self-efficacy, the more active and diligent the efforts. When faced with difficulties, the individual has great doubts about his ability to reduce his efforts or give up altogether. The purpose of this study was to analyze the effect of self-efficacy, job insecurity, and job development on job satisfaction through job motivation at PT. Tanjungpinang Beautiful Fashion Swakarya totaling 132 people. The sample used in this study is the entire population of 132 employees of PT. Beautiful DIY Clothing Tanjungpinang. In this study, the sampling technique used was nonprobability sampling with the technique taken, namely saturated sampling (census). The research method uses an associative method with a quantitative approach with analysis of Partial Least Square (PLS) analysis techniques with the SmartPLS Version 4.0 program. The results of this study state that the variable self-efficacy has a positive and significant effect on job satisfaction. The job insecurity variable has a positive and significant effect on job satisfaction. The job development variable has a positive and significant effect on job satisfaction. The job motivation variable has a positive and significant effect on job satisfaction. The self-efficacy variable has a positive and significant effect on job motivation. The job insecurity variable has a positive and significant effect on job motivation. The job development variable has a positive and insignificant effect on job motivation. The job motivation variable is able to mediate the effect of self-efficacy on job satisfaction. The job motivation variable has not been able to mediate the effect of job insecurity on job satisfaction. The job motivation variable has not been able to mediate the effect of job development on job satisfaction.